Physical, mechanical and morphological properties of laminated bamboo hybrid composite: a potential raw material for furniture manufacturing. (15th July 2020) - Siti Suhaily, S; Islam, Md Nazrul; Asniza, M; Rizal, Samsul; Abdul Khalil, H P S
Abstract: Laminated hybrid composites were prepared by incorporating dry bamboo strips and oil palm trunk veneer (OPTV) to form five-layer laminated composites. Two different species of bamboo were used including Dendrocalamus asper and Gigantochloa levis to explore their potential for furniture manufacturing. Influence of the bamboo species along with the different arrangements of lamination on the physical, mechanical and morphology properties of the hybrid laminated composites were investigated via scanning electron microscope (SEM), density, water absorption (WA), thickness swelling (TS) as well as impact and hardness strength test. Morphological study showed that filling up of surface cavity by adhesive improved the bonding strength between the surfaces of the bamboo strips and OPTV in the laminated hybrid composites. Additionally, different layer arrangements affected the mechanical properties, i.e., perpendicular arrangement exhibited higher strength compared to the parallel arrangement for both hardness and impact strength. The species of bamboo did not show significant impact on the density for different layer arrangements. Thus, test results clearly indicated that bamboo strips and OPTV hybrid composites could be used as an alternative to wood-based composites for furniture manufacturing.